Há um direito por vir: um direito capaz de dar conta do questionamento do paradigma antropocêntrico em que está inserida a modernidade e da emergência de pautas para além do humano - Azevedo, Maria Cândida Simon (Universidade do Vale do Rio dos Sinos, 2024)
With the intensification of ecological problems, the emergence of questioning of thoughts long inscribed in the bases of societies and the need to compatible different thoughts in plural societies, social, ethical, theoretical, and political movements begin to emerge that seek to deconstruct the traditional anthropocentric understanding of world, in which only human beings would be inscribes. The present research intends, therefore, to carry out, through an approach of critical theory, diagnosis and prognosis, in the style of the dialectical method, an analysis of the current transformations in Law, arising from these disputes between the dichotomy of anthropocentrism versus non-anthropocentrism. To this end, the research intends to answer the following question: what is the meaning of a Law beyond the human, capable of addressing the questioning of the anthropocentric paradigm in which modernity is inserted, the emergence of agendas beyond the human and compatibility between different thoughts? The hypothesis that will be put to the test is that the construction of a Law beyond the human must involve a multinormative understanding of society, in addition to being established on non-anthropocentric bases. This means opening the rationality inherent to Law to other ways of understanding the world, in addition to the traditional Western one, through an exercise of reason itself, which is capable of pointing Law towards a nonanthropocentric (beyond human) understanding of the world. To develop the objective of the text, as well as to adequately respond to the research problem, the text was divided into two chapters. The first seeks to produce a diagnosis of the current conjecture of disputes surrounding anthropocentrism, as a result of the demands of non-anthropocentric movements. The second intends to develop the proposed hypothesis, using the conclusions of the analysis established in the previous chapter, taken to the sphere of Law. The considerations raised here, and the intentions established with the aim of clarifying the demands of a nonanthropocentric movement are extremely important, seeking to understand the current conjecture of the movement, regarding one of its main objectives, that is, establishing a minimum level of moral and legal recognition for subjects beyond the human.
Keywords: Direito; Ecologia; Movimentos para além do humano; Novos sujeitos; Despersonalização da propriedade; Law; Ecology; Movements beyond the human; New subjects; Property depersonalization; ACCNPQ::Ciências Sociais Aplicadas::Direito